Analysis Of Parent Companion Of 33 Boddie Public Elementary School Students Pangkajene And Islands District On Activities Learning From Home During The Covid-19 Pandemic - Anirma Musfira Asniar; Widya Karmila Sari Achmad; Hotimah Hotimah (International Journal of Elementary School Teacher, 2022)
The study aims to know the parent-parents of the 33 boddie county of pangkajene and islands on learning activities at the time of pandemic covid-19. For the results of the 33 boddie county primary student assistance analysis of pangkajene and islands counties on home learning activities during the covid-19 pandemic. This study, using a kind of quantitative research with a descriptive quantitative study method. Based on the results of the normality test with the shapiro-wilk test using a statistical application on SPSS 25 as the significance of a statusary on the Banks of class iii is 0.198 >0.05 and an 472>0.05. Based on the results of the hypothesis test with tests a-t one test samples using version 25's statistical application version 25 acquired value of 0.001>0.05. Thus, ho was rejected and ha received and it may be concluded that there was a significant influence by female primary school parents of 33 boddie county pangkajene and islands of the study activity from home during the covid-19 pandemic. Parent-parents of class iii and iv SDN 33 boddie counties pangkajene and islands have an average of 73.7. As for the optimally provided form of parenting in the optimal category of 73.7% (38 students), that is, as many as 38 students get parents to give good attention to their children (1) provide guidance, (2) give counsel, (3) provide motivation and appreciation, (4) provide child care, and (5) provide child supervision. There is a positive and significant link between student chaperones SDN 33 boddie district pangkajene and islands in the learning process from home at the time of the covid-19 pandemic suggested by testing t-one test of 0.001 0.05 so that the parent is acceptable